ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN MELALUI CITRA RESTORAN SEBAGAI VARIABEL INTERVENING - Hanani, Zati; Ferdinand, Augusty Tae (Faculty of Economics and Business Diponegoro University, 2018)
The purpose of this study is to explain the effect of product quality, service quality and restaurant atmosphere to influence purchase decisions, where restaurant image is used as an intervening variable to the purchase decision at Pondok Ijo Weleri Kendal Restaurant.This research is done by taking sample using purposive sampling technique, that is consumers who have visited and bought some food in Pondok Ijo Restaurant at least once with average of age 14 years old up to 40 years and above. Data collection was obtained from 100 consumers of Pondok Ijo Restaurant by giving questionnaires which consist of open questions which is analyzed qualitatively, and the answer of the closed questions were analyzed using Multiple Linear regression method using SPSS 22 program.The results of the analysis show that product quality, service quality and store atmosphere have a positive and significant influence on the restaurant image, then restaurant image has a positive and significant influence on purchase decisions.